Community Empowerment Through Homegrown Medicinal Plants and The "Wedang Uwuh" Herbal Beverage Cultivation in Seketi Hamlet - Juliani Pudjowati; Thariq Abdurrahman; Enjelita Putri Pratiwi; Rizky Nugraha Baqi; Anggun Kumala Syafitri (Journal of Community Practice and Social Welfare, 2021)
Rural community empowerment is an effort to develop independence and community welfare through the improvement of knowledge, attitudes, skills, behaviour, abilities, awareness, and resource utilization. This is carried out by establishing policies, programs, activities and assisting with the problems related to the priority needs of the community to increase community activities through the cultivation of homegrown medicinal plants. The homegrown medicinal plants (TOGA) are traditional medicinal plants. These medicinal plants are used for making Wedang Uwuh. The ingredients consist of various types of spices namely: ginger, cloves, nutmeg, lemongrass, cardamom, cinnamon, sappanwood, and rosella. The method of implementation used is through the diffusion of knowledge and direct practice. These activities were carried out for the residents of Seketi Hamlet. The results of the activities that have been carried out in Seketi Hamlet are as follows: the community gets insight into TOGA plants; people acquire skills in how to process TOGA into Wedang Uwuh herbal beverage which can help increase endurance (immunomodulators) to protect against Covid-19 pandemic; adding or increasing community activities through the use of house yards as TOGA growing media. Therefore, it is necessary for the Head of Seketi Hamlet to consider doing several things, namely the provision of advanced programs via entrepreneurship training to produce superior products from TOGA yields, and community cooperation in the continuous care of the “Seketi Hamlet Health Garden” for long term benefits.